The handbook of nanotechnology : business, policy, and intellectual property law / John C. Miller [and others] ; with an editorial contribution by Mark Graffagnini. - Miller, John C. (Wiley, 2005)
The Handbook of Nanotechnology Business, Policy, and IP Law offers a thorough analysis of the controversial issues associated with the commercial application of nanotechnology: intellectual property and patents, financing and legal concerns, regulatory measures particularly in the field of nanomedicine, and environmental regulations.